Procuring food stocks under World Trade Organization farm subsidy rules: Finding a permanent solution - Glauber, Joseph W.; Sinha, Tanvi (International Institute for Sustainable Development, 2021)
This report summarizes the current negotiating proposals at the World Trade Organization that include among others: exempting food bought at administered prices under public stockholding programs from the calculation of trade-distorting support; revisiting the external reference price in the calculation of market price support; taking into consideration excessive rates of inflation; redefining eligible production; including new programs; and expanding product coverage. The report then analyzes the evolving market and context, including for key commodities such as rice and wheat. Finally, it examines the advantages and disadvantages of various possible ways in which the public stockholding issue could be addressed and identifies possible ways forward.